Analysis of the prevalence of drug-resistant hepatitis B virus in patients with antiviral therapy failure in a Chinese tertiary referral liver centre (2010–2014). (March 2017) - Meng, Tian; Shi, Xiaofeng; Gong, Xuyang; Deng, Haijun; Huang, Yao; Shan, Xuefeng; Shan, Youlan; Huang, Ailong; Long, Quanxin
Highlights: Long-term observation of hepatitis B virus drug resistance. l -Nucleoside genotypic drug resistance was the most common resistance phenotype. Resistance rates of different drugs showed no statistical difference between genotype B and C patients. Resistance rates to 3TC, LdT and ETV in HCC, LC and CHB patient groups showed statistical differences. Abstract: Objectives: To study the prevalence of drug-resistant HBV in patients with therapy failure in a Chinese tertiary referral liver centre. Methods: 1223 HBV-infected patients who underwent genotypic resistance testing between 2010–2014 were studied. Results: 3TC genotypic resistance was the most common (46.5%), followed by LdT resistant (46.2%), ETV intermediate (37.9%), ADV resistant (11.4%), TDF intermediate (11.4%) and ETV resistant (1.7%). The 3TC resistance rate increased from 39.8% in 2010 to 56.6% in 2013, before decreasing to 49.5% in 2014, evidence of a lagging effect ofl -nucleoside consumption. M204I, N236T and L180M + M204V + V173L/S202G were the most common substitutions forl -nucleoside (3TC and LdT), ADV and ETV genotypic resistant phenotypes, respectively. 3TC-exposed patients showed a high multiple genetic resistance rate (3TC-resistant + LdT-resistant + ETV intermediate; 58.8%). Resistance rates to 3TC, LdT and ETV in HCC patients were significantly higher than in cirrhosis and CHB patients. Resistance rates to different drugs showed no statistical difference between genotype B and C patients, whilst some amino acid substitution showed genotype bias, e.g. N236T incidence in genotype B was significantly higher than in genotype C (43.2% vs. 5.9%; P < 0.0001), and genotype C isolates had a significantly higher A181V/T incidence than genotype B (54.9% vs. 19.3%; P < 0.0001). Conclusions: 3TC genotypic resistance was most common in this centre, whilst ETV had the lowest resistance rate. HBV genotypes had no impact on antiviral drug resistance, except for some drug resistance substitutions bias. Optional initial therapy and subsequent rescue treatment should be based on knowledge of nucleos(t)ide analogue resistance.